A multi-strategy platform for Q-markers screening and quality control of Wuzi Yanzong Wan based on fingerprint and network pharmacology - Bao-Hua Dong; Jie Wu; Ying Peng; Yun-Xiu Jiang; Ma-Yi-Jie Cao; Yu Huang; Chang-Jiang Hu; Ling-ying Yu; Zhi-Min Chen (Arabian Journal of Chemistry, 2024)
Wuzi Yanzong Wan (WZYZW) is a classic formula for tonifying the kidneys in Traditional chinese medicine (TCM) and is widely used clinically in diseases of the reproductive system, immune system and nervous system. Therefore, the quality control and prediction quality markers (Q-markers) of WZYZW is of positive significance.In this study, We first established the fingerprints, calibrated 28 common peaks, identified 12 common peaks of gallic acid, geniposidic acid, chlorogenic acid, ellagic acid, rutin, hyperoside, verbascoside, astragalin, kaempferol, schisandrol A, schisandrol B and schisandrin B, and the similarity was greater than 0.9 of 10 batches.Then, withing network pharmacology, we screened 41 core targets such as PIK3CA, AKT1, PIK3CB, potential pathways such as pathways in cancer and PI3K-Akt signalling pathway of 12 components. The results showed that they were tightly connected to predicated targets and pathways. Finally, by using the hyperoside as internal reference standard, a Quantitative analysis of multi-components (QAMS) for WZYZW was established to determine the contents of WZYZW. The percent difference(%) showed that there was no significant difference between the quantitative results of external standard method (ESM) and QAMS method. Contents of the 11 components above were 0.0091 ∼ 0.0185 %, 0.1019 ∼ 0.1361 %, 0.0518 ∼ 0.0718 %, 0.0130 ∼ 0.0320 %, 0.0084 ∼ 0.0190 %, 0.0621 ∼ 0.1192 %, 0.0127 ∼ 0.0419 %, 0.0006 ∼ 0.0089 %, 0.0212 ∼ 0.0261 %, 0.0061 ∼ 0.0400 %, 0.0084 ∼ 0.0103 %, respectively. Overall, the method developed was applied to the quality evaluation and Q-markers research of WZYZW as well as provided guiding significance for the Q-marker research of TCM.